Why People Hesitate To Help: A Relationship Between Stigma and Help-Giving Attitude - Franz A. Nurdiyanto; Diana Setiyawati (ANIMA Indonesian Psychological Journal, 2017)
Mental disorders have become a prominent global burden of disease and their prevalent rate has increased by 37.6% in 1990-2010. In Indonesia, the prevalence of people with severe mental illness was approximately 1-2 out of 1,000 people. Unfortunately, the provisions of mental health services are still insufficient compared to the public need. It is difficult to find mental health services. People with mental illness also rarely receive an appropriate treatment they need. Furthermore, misconceptions on mental illness have made the society hesitate to help. This research aimed to investigate the correlation between public stigma and mental health help-giving attitude. There were 203 participants (Male n = 44) from psychology, medicine, and nursing programs involved in the research. They completed public stigma scale and attitude towards mental health help-giving scale. A correlational analysis using the Charles Spearman’s rank-order correlation revealed a negative correlation of - .47 (p < .05). Based on the result, public stigma was related to mental health help-giving. There was no difference between males and females in mental health help-giving.